Inovasi Layanan Perpustakaan Dalam Masa Pandemi Covid-19: Studi Kasus di UPT Perpustakaan Proklamator Bung Karno Blitar - Friska Fauzi; Pricilia Dyah Prastiti; Gading Titiswari (Ikatan Pustakawan Indonesia, 2021)
Library must inovate in order to keep gave services to people in Covid-19 pandemic era.Library must inovate in order to keep gave services to people in Covid-19 pandemic era. This study aims to determine the service innovation carried out by UPT Proklamator Bung Karno Library during the Covid-19 pandemic. The research data were processed using a qualitative approach with descriptive analysis. The data was collected by observation techniques, interviews, and documentation study on UPT Proklamator Bung Karno Library’s website and social medias. The results showed that: UPT Proklamator Bung Karno Library had made service innovations in various aspects during the Covid-19 pandemic. First, do online loan system. Second, open online member registration. Third, create live chat application on the website. Fourth, provide e-book collections on the website and Google play store application. Fifth, hold webinars and online discussions.